Labour protection and productivity in the European economies: 1995-2005 - Damiani, Mirella; Pompei, Fabrizio (Munich, 2009)
"The present study examines cross-national and sectoral differences in multifactor productivity growth in sixteen European countries from 1995 to 2005. The main aim is to ascertain the role of flexible employment contracts and collective labour relationships in explaining the ample differentials recorded in the European economy. Research Findings We use the EU KLEMS database for growth accounting and a broad set of indicators of labour regulations, covering two distinct ‘areas’ of labour regulation: employment laws and collective relations laws. This comprehensive approach allow us to consider arrangements that regulate allocation of labour inputs (fixed-term, part-time contracts, hours worked) and of payoff and decision rights of employees. We find that, since 1995, European countries have not followed similar patterns of growth. A large number of variations between European economies are caused by deep differentials in multifactor productivity and part of this heterogeneity is caused by sectoral diversities. We show that, in labour-intensive sectors such as services, fixed-term contracts, which imply shorter-term jobs and lower employment tenures, may discourage investment in skills and have detrimental effects on multifactor productivity increases. We also find that some forms of labour regulation and arrangements that give a ‘voice’ to employees mitigate these perverse effects on efficiency patterns. Employment protection reforms which slacken the rules of fixed-term contracts cause potential drawbacks in terms of low productivity gains. More stringent regulation of these practices, as well as a climate of collective relations, sustain long-term relationships and mitigate these negative effects."